2021
DOI: 10.3389/fgene.2021.616110
|View full text |Cite
|
Sign up to set email alerts
|

CDK4 Amplification in Esophageal Squamous Cell Carcinoma Associated With Better Patient Outcome

Abstract: In the present study, we aimed to investigate the clinical and prognostic values of CDK4 amplification and improve the risk stratification in patients with esophageal squamous cell carcinoma. CDK4 amplification was analyzed by fluorescence in situ hybridization using tissue microarray consisting of representative tissues of 520 patients with esophageal squamous cell carcinoma, and its correlation with clinicopathological features and clinical outcomes were evaluated. CDK4 amplification was found in 8.5% (44/52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Gao et al [ 64 ] demonstrated that High Mobility Group Box 3 ( HMBG3 ) may be a potential molecular marker for predicting the prognosis of ESCC patients. According to Huang et al [ 65 ], cyclin-dependent kinase 4 ( CDK4 ) amplification was identified as an independent prognostic factor for survival, which could be incorporated into the tumor-node-metastasis staging system to refine risk stratification of patients with esophageal squamous cell carcinoma. Ling et al [ 66 ] suggested that MutS Homolog 2 ( MSH2 ) methylation in the plasma would be a good predictor of DFS for these ESCC patients before oesophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [ 64 ] demonstrated that High Mobility Group Box 3 ( HMBG3 ) may be a potential molecular marker for predicting the prognosis of ESCC patients. According to Huang et al [ 65 ], cyclin-dependent kinase 4 ( CDK4 ) amplification was identified as an independent prognostic factor for survival, which could be incorporated into the tumor-node-metastasis staging system to refine risk stratification of patients with esophageal squamous cell carcinoma. Ling et al [ 66 ] suggested that MutS Homolog 2 ( MSH2 ) methylation in the plasma would be a good predictor of DFS for these ESCC patients before oesophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major subtypes of Esophageal cancer (EC), esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) (Ye et al, 2021). In China, more than 90% of esophageal cancer cases are ESCC (Zhang X. et al, 2021). EC as a whole remains a significant challenge globally, having the 8 th highest incidence and the 6th highest mortality worldwide killing over 500,000 people in 2020 (Sung et al, 2021).…”
Section: Introductionmentioning
confidence: 99%